2000
DOI: 10.1017/s0021963099005302
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation Seeking and Hyperactivity in Children with ADHD

Abstract: Thirty hyperactive and 30 non-hyperactive children were confronted with a delay, consisting of a waiting situation of 15 minutes, either with or without extra stimulation provided by the presentation of a videotape. The behaviour of the child during the waiting period was videotaped and later coded by two naive observers. In line with theories that emphasise the stimulation-seeking function of hyperactive behaviours, such as the optimal stimulation account and the delay aversion theory, a group by stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
65
3
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 23 publications
(28 reference statements)
9
65
3
2
Order By: Relevance
“…This impulsivity leads to several detrimental effects: Children with ADHD show risky behavior (i.e., fast driving; Jerome et al 2006), sensation seeking (Antrop et al 2000), are responsive to immediate rewards (Douglas and Parry 1994), and are less able to delay gratification or resist temptation .…”
Section: Self-control In Children With Adhdmentioning
confidence: 99%
“…This impulsivity leads to several detrimental effects: Children with ADHD show risky behavior (i.e., fast driving; Jerome et al 2006), sensation seeking (Antrop et al 2000), are responsive to immediate rewards (Douglas and Parry 1994), and are less able to delay gratification or resist temptation .…”
Section: Self-control In Children With Adhdmentioning
confidence: 99%
“…While DSM-IV criteria stipulate that ADHD symptoms must be present across different conditions it is clear, as noted above, that situational factors influence behavior and may in part account for some of the variance between parent and teacher reports of ADHD symptoms. For example, performance tends to be poorer in the afternoon compared to the morning (Dane, Schachar, & Tannock, 2000;Porrino et al, 1983); under low levels of stimulation (Antrop, Roeyers, Van Oost, & Buysse, 2000); when task complexity taxes organizational abilities (Douglas, 1983); and when restraint is required (Barkley & Ullman, 1975;Luk, 1985). Behavioral problems are far more likely to emerge when a child must persist in a work-related task (e.g., homework, household chore) or in a setting that constrains their behavior (e.g., church, restaurant) than in unrestricted, free play situations (Barkley & Edelbrock, 1987;Breen & Altepeter, 1990).…”
Section: Subject and Contextual Influencesmentioning
confidence: 99%
“…This theory is 'bottom-up' as it does not have a major focus on cognitive processes (Solanto et al, 2001). Antrop, Roeyers, Van Oost, and Buysse (2000) found that, in a waiting situation, children with ADHD demonstrated more activity in a delay situation without a stimulating distracter than in a delay situation with a distracter. Similarly, state-regulation dysfunction theories focus on levels of arousal or energy.…”
mentioning
confidence: 91%